Self : Ancient and Modern Insights about Individuality, Life, and Death. - Sorabji, Richard (Oxford University Press, Incorporated, 2006)
Richard Sorabji presents a brilliant exploration of the history of our understanding of the self, which has remained elusive and mysterious throughout the spectacular development of human knowledge of the outside world. He ranges from ancient to contemporary thought, Western and Eastern, to reveal and assess the insights of a remarkable variety of thinkers. On this basis he rejects the common idea that the self is an illusion, and develops his own original conceptionof the self as essential to our ownership of our experience and our apprehension of the world.